2013
DOI: 10.1038/ejhg.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Nebulin (NEB) mutations in a childhood onset distal myopathy with rods and cores uncovered by next generation sequencing

Abstract: Recessive nebulin (NEB) mutations are a common cause of nemaline myopathy (NM), typically characterized by generalized weakness of early-onset and nemaline rods on muscle biopsy. Exceptional adult cases with additional cores and an isolated distal weakness have been reported. The large NEB gene with 183 exons has been an obstacle for the genetic work-up. Here we report a childhood-onset case with distal weakness and a core-rod myopathy, associated with recessive NEB mutations identified by next generation sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 18 publications
3
44
0
Order By: Relevance
“…Recently, Scoto et al (2013) reported a childhood-onset distal myopathy with rods and cores, caused by compound heterozygous NEB variants (the Ashkenazi founder deletion of exon 55 and a frameshift mutation in the alternatively spliced exon 172, family CR2, Table 2). In the current paper, we report compound heterozygous NEB variants identified in two French families in which the patients had a similar distal phenotype (F282, F410; Table 2).…”
Section: The Spectrum Of Myopathies Caused By Variants In Nebmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Scoto et al (2013) reported a childhood-onset distal myopathy with rods and cores, caused by compound heterozygous NEB variants (the Ashkenazi founder deletion of exon 55 and a frameshift mutation in the alternatively spliced exon 172, family CR2, Table 2). In the current paper, we report compound heterozygous NEB variants identified in two French families in which the patients had a similar distal phenotype (F282, F410; Table 2).…”
Section: The Spectrum Of Myopathies Caused By Variants In Nebmentioning
confidence: 99%
“…Other, less common entities include early-onset distal myopathy without nemaline bodies [Wallgren-Pettersson et al, 2007], a distal form of NM [Lehtokari et al, 2011], core-rod myopathy with generalized muscle weakness [Romero et al, 2009], and a childhood-onset distal myopathy with rods and cores [Scoto et al, 2013]. …”
Section: Introductionmentioning
confidence: 99%
“…20 In 2 cases, next-generation sequencing analysis has subsequently allowed comprehensive analysis of NEB. 21 Histologic analysis. Muscle biopsies were reviewed and classified according to criteria suggested by Dubowitz et al 22 : (1) nemaline myopathy (NM); (2) centronuclear myopathy (CNM); (3) "core myopathies," including central core disease and multiminicore disease; (4) FTD; (5) type 1 fiber predominance/ uniformity; and (6) nonspecific myopathic changes (NSMC).…”
Section: Methodsmentioning
confidence: 99%
“…8 Some patients present with a distal myopathy, with their skeletal muscle biopsies containing nemaline bodies, both nemaline bodies and cores, or no nemaline bodies. 9,10 Rare cases of core-rod myopathy with generalised muscle weakness may also be caused by NEB variants. 11 ACTA1: over 200 different variants identified, with the majority causing nemaline myopathy, or nemaline myopathy with other features (eg cores, actin aggregates, intranuclear rods and zebra bodies).…”
Section: Mutational Spectrummentioning
confidence: 99%